Pengabdian Masyarakat LP2M IAIN Palangka Raya dalam Persepsi Masyarakat Muslim Desa Pangi - Muhammad Norrahmani; Abd. Rahman (Syams: Jurnal Kajian Keislaman, 2020)
This paper focuses on knowing the perceptions of the Muslim community in Pangi village of community service activities by LP2M IAIN Palangka Raya in the field of religious development, with the aim of providing input to LP2M and da'wah stakeholders and policy makers to further provide guidance in villages that are in need, especially Pangi Village, Banama Tingang District, Pulang Pisau Regency. To get results that are in line with the research objectives, this paper uses a qualitative descriptive approach to obtain oral data from informants. This article concludes that the public perception of the religious guidance program carried out by LP2M IAIN Palangka Raya is very positive and the program is an activity desired by the Muslim community of Pangi Village, Pulang Pisau Regency, considering that in that village Islam is a minority religionus and the absence of these activities before. The community is very enthusiastic about the religious guidance activities carried out by LP2M IAIN Palangka Raya.